FREQUENCY OF NON-UNION IN OPEN TIBIAL SHAFT FRACTURES PRESENTING IN TERTIARY CARE CENTER OF PUNJAB TREATED WITH AO FIXATOR - SIDDIQ, MZ; RAZZAQUE, MA; ATIF, M; AHMED, J; REHMAN, MU; AHMED, B (Biological and Clinical Sciences Research Journal, 2023)
This study aimed to evaluate the frequency of non-union in open tibial shaft fractures presenting in the Tertiary Care Centre of Punjab, treated with an AO fixator. A descriptive study was conducted in the Department of Orthopedics, Aziz Bhatti Shaheed Teaching Hospital, Gujrat & Bakhtawar Amin Hospital Multan from 01-12-2020 to 30-09-2021. A total of 93 cases were selected for the study. Demographic data of patients were noted. All the patients were managed by the same orthopedic department team, including the candidate led by the consultant, to keep results unbiased. Patients ranged between 18-70 years of age, with a mean age of 38.12±11.12 years. There were 65 males (69.9%) and 28 females (30.1%). 33 patients (35.5%) were admitted 24-48 hours after injury. 32 patients (34.4%) had a third upper fracture. Non-union was found in 39 patients (41.9%) and malunion in 2 patients (2.1%). Based on the results, the AO external fixator is a good and viable option for open tibial shaft fractures. This is a versatile, cost-effective, satisfactory, and reliable method of stabilization of open fractures.